Iron contributes to photoreceptor degeneration and Müller glia proliferation in the zebrafish light-treated retina. (March 2022) - Boyd, Patrick; Hyde, David R.
Abstract: Zebrafish possess the ability to completely regenerate the retina following injury, however little is understood about the damage signals that contribute to inducing Müller glia reprogramming and proliferation to regenerate lost neurons. Multiple studies demonstrated that iron contributes to various retinal injuries, however no link has been shown between iron and zebrafish retinal regeneration. Here we demonstrate that Müller glia exhibit transcriptional changes following injury to regulate iron levels within the retina, allowing for increased iron uptake and decreased export. The response of the zebrafish retina to intravitreal iron injection was then characterized, showing that ferrous, and not ferric, iron induces retinal cell death. Additionally, iron chelation resulted in decreased numbers of TUNEL-positive photoreceptors and fewer proliferating Müller glia. Despite the contribution of iron to retinal cell death, inhibition of ferroptosis did not significantly reduce cell death following light treatment. Finally, we demonstrate that both the anti-ferroptotic protein Glutathione peroxidase 4b and the Transferrin receptor 1b are required for Müller glia proliferation following light damage. Together these findings show that iron contributes to cell death in the light-damaged retina and is essential for inducing the Müller glia regeneration response. Highlights: Intravitreal iron injection induces retinal cell death in the zebrafish retina. Iron contributes to photoreceptor death in the light-damaged zebrafish retina. Ferroptosis inhibition does not reduce light-damaged zebrafish retinal cell death. Tfr1b and Gpx4b are required for Müller glia proliferation following retinal damage.